Bioeconomic evaluation of allelopathic crop leachates integrated with reduced doses of herbicide for horse purslane management in maize under field conditions - N. Mushtaq,Muhammad (2020)
Abstract Background: Continuous use of commercial herbicides is posing a severe threat to environment and creating herbicide resistant weeds. Allelopathy offers a promising alternative to commercial herbicides for sustainable weed management. The farmers are highly concerned with maximum yield as well as cost of the weed control techniques. Objective: To investigate economic and weed control efficiency of allelopathic crop water leachates mixed with lower rates of herbicide. Methods: Rapeseed (Brassica napus L.), sunflower (Helianthus annuus L.) and sorghum (Sorghum bicolor L.) crop leachates (18 L ha-1 each) tank mixed with lower doses (25, 33 and 50% of recommended dose) of S-metolachlor+atrazine were sprayed as pre-emergence for horse purslane (Trianthema portulacastrum L.) management in maize (Zea mays L.). Label dose (1,080 g a.i. ha-1) of herbicide (S-metolachlor+atrazine) and a weedy check treatment were also maintained. Results: The results showed that rapeseed+sunflower+sorghum allelopathic leachates mixed with half dose (540 g a.i. ha-1) of S-metolachlor+atrazine was effective against horse purslane and increased maize yield (grain) by 45% and 5% as compared with control and label dose of herbicide, respectively. Likewise, economic analysis showed that the same treatment was most economical with 40% and 9% higher net benefits than control and label dose of herbicide, respectively and 2407% marginal rate of return. It also gave an additional benefit of US$ 24.07 for investment of every US$1. Conclusions: By using this technique, herbicides use can be minimized by 50% for sustainable weed management without compromising maize yield and net benefits.